2020
DOI: 10.1037/amp0000464
|View full text |Cite
|
Sign up to set email alerts
|

Parental ethnic-racial socialization practices and children of color’s psychosocial and behavioral adjustment: A systematic review and meta-analysis.

Abstract: Despite growing support for the role of ethnic-racial socialization in minority youth development, no integrative research previously examined the practical significance of parental ethnic-racial socialization on minority youth's psychological and behavioral well-being. This meta-analysis synthesizes the existing literature across 102 empirical studies. The authors examined the nuanced ways in which specific dimensions of parental ethnic-racial socialization operate to influence development in youth of color.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
269
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 221 publications
(291 citation statements)
references
References 103 publications
19
269
0
3
Order By: Relevance
“…Yet, racism needs to be more intentionally addressed in nursing and medical school curricula. At the same time, numerous studies support the existence of relational and cultural assets that serve as protective mechanisms for racially marginalized individuals (Anderson, Anyiwo, Gaylor-Harden, Jones, & McKenny, 2019;Trent et al, 2019;Vasquez-Tokos & Norton-Smith, 2016;Wang, Henry, Smith, Huguley, & Guo, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, racism needs to be more intentionally addressed in nursing and medical school curricula. At the same time, numerous studies support the existence of relational and cultural assets that serve as protective mechanisms for racially marginalized individuals (Anderson, Anyiwo, Gaylor-Harden, Jones, & McKenny, 2019;Trent et al, 2019;Vasquez-Tokos & Norton-Smith, 2016;Wang, Henry, Smith, Huguley, & Guo, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Ethnic‐racial socialization, defined as “the mechanisms through which parents transmit information, values, and perspectives about ethnicity and race to their children” (Hughes et al., , p. 747), has received increased attention as a developmental and cultural asset for children of color that buffers against racist encounters and aids in effective processing of stereotypes and microaggressions (Berkel et al., ; Neblett, Rivas‐Drake, & Umaña‐Taylor, ). Although researchers generally agree that ethnic‐racial socialization has important consequences for child outcomes (Stevenson, Herrero‐Taylor, Cameron, & Davis, ; Yasui, , Wang, Henry, Smith,Huguley, & Guo, ), inconsistent results across studies may indicate effect variations as a function of several key moderators, especially regarding academic outcomes. While several studies have demonstrated positive associations between the global construct of ethnic‐racial socialization and academic motivation (Brown, Linver, Evans, & DeGennaro, ; Wang & Huguley, ), others have found the effects on academic performance vary depending on the dimensions of socialization considered (Brown et al., ; Caughy, O'Campo, Randolph, & Nickerson, ).…”
Section: Ethnic‐racial Socialization and Child Developmentmentioning
confidence: 99%
“…A recent meta-analysis found that racial socialization messages that promote feelings of pride about being Black (e.g., "You should be proud to be Black") are the strongest predictor of adaptive racial identity attitudes (e.g., centrality and private regard) among Black youth (Huguley et al 2019). In addition, messages about racial pride are commonly linked with positive wellbeing among Black youth (Wang et al 2020). The relationship between racial socialization and wellbeing has been less thoroughly examined, but scholars theorize that it works through intermediary channels like racial identity (Anderson and Stevenson 2019).…”
Section: Racial Socialization and Gendered Racial Socializationmentioning
confidence: 99%